ANALISIS HAK AKSES TERHADAP INFORMASI YANG TERDAPAT DALAM REKAM MEDIS DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 17 TAHUN 2023 TENTANG KESEHATAN - Firman Nurdiyansyah Sunandar, (Journal of Innovation Research and Knowledge, 2024)
It is mandatory for medical facilities to provide emergency care. The role of the medical record is to serve as a guide for every step of health care that is required in medical practice. It is carried out by medical staff members, assessing their professionalism, cleanliness, and accuracy. Furthermore, this also serves as a gauge of the quality of health care. One relevant and appropriate way to ensure that every person understands the comprehensive and reliable information provided about health services is to create a written document. An effective medical record can help patients receive professional care while also reducing quality, duration, and dose as well as aiding in data collection, pidana, and etik code entry processes. In paragraph (1) of Section 297 of the Health Law, it is stated that the medical records belong to the Health Care Facilities Department. Article 297 paragraph (2) Health Law was then discussed